The Emotional Lexicon Used by Male and Female Communication: Study of Balinese Language Used in South Kuta-Bali - I Gusti Ayu Vina Widiadnya Putri; I Dewa Ayu Devi Maharani Santika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The aims of this research is to analyse about the differences of emotional lexicon used by male and female communication in South Kuta-Bali when they used Balinese language in their daily interaction. The scope of male and female is closely related to the social behavior which includes the social identity of male and female in society and this becomes the basis of how the language is used in this context of social. This research is interested to uncover more how people use language in terms of expressing their emotional in social interaction. This study is a sociolinguistic approach used the theory from Hickey, Raymon (2010). The data source in this study is the south Kuta community who use Balinese language in social interactions. The Data collection is done by observation, interview, recording and note taking and descriptive qualitative method is applied to analyze the data. The result of the analysis found that the emotional lexical is used by the male and female in their social interaction, it could mention that both Augmentatives and Euphemisms is used by male and female in their social interaction however the augmentative is mostly used by female in informal occasion. Balinese female often used prohibition instead of imperative in expressing her idea about ordering someone to do something. In the other hand, the male directly used imperative sentence in ordering something. He usually does not use many awkwardness to say his point in a conversation. This may be considered that the male often go to the straight point when expressing his idea. Keywords: Emotional Lexicon, Male and Female